2019
DOI: 10.1002/jcp.28570
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of SDF‐1/CXCR4 reduces adhesion‐mediated chemoresistance of multiple myeloma cells via interacting with interleukin‐6

Abstract: Resistance to chemotherapy represents a major cause for treatment failure in multiple myeloma (MM). Herein, this study was conducted to explore the effect of SDF-1/CXCR4 and interleukin-6 (IL-6) in MM cell adhesion-mediated chemoresistance. Enzyme-linked immunosorbent assay was applied to detect expressions of SDF-1α and IL-6 in MM patients and healthy controls. RPMI-8226 cells and isolated bone marrow stromal cells (BMSCs) were stimulated using recombinant SDF-1α and IL-6. Effect of cocultured BMSCs and RPMI-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 35 publications
0
15
0
1
Order By: Relevance
“…For example, targeting IL6 (e.g., Johnson and Johnson’s drug sirukumab), or the IL6 receptor (e.g., Regeneron’s sarilumab) could be tailored perhaps by using BMAT biomarkers ( 62 ), knowing now that BMAds, especially myeloma-associated adipocyte lineage cells, are a source of IL6. Better alignment with patient populations for enhanced precision medicine could also be considered based on our data, for therapies targeting the CXCL12/CXCR4 axis, such as the CXCR4 inhibitor AMD3100 (plerixafor) ( 63 ), or the CXCL12 antagonist NOX-A12 ( 64 ). Our data may also help explain the ability of treatment with plerixafor to overcome bortezomib resistance and mobilize stem cells and immune cells, which was recently reported in a phase I/II trial ( 65 ), by providing new insight into the players in the bone marrow niche involved in this pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, targeting IL6 (e.g., Johnson and Johnson’s drug sirukumab), or the IL6 receptor (e.g., Regeneron’s sarilumab) could be tailored perhaps by using BMAT biomarkers ( 62 ), knowing now that BMAds, especially myeloma-associated adipocyte lineage cells, are a source of IL6. Better alignment with patient populations for enhanced precision medicine could also be considered based on our data, for therapies targeting the CXCL12/CXCR4 axis, such as the CXCR4 inhibitor AMD3100 (plerixafor) ( 63 ), or the CXCL12 antagonist NOX-A12 ( 64 ). Our data may also help explain the ability of treatment with plerixafor to overcome bortezomib resistance and mobilize stem cells and immune cells, which was recently reported in a phase I/II trial ( 65 ), by providing new insight into the players in the bone marrow niche involved in this pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Our data may also help explain the ability of treatment with plerixafor to overcome bortezomib resistance and mobilize stem cells and immune cells, which was recently reported in a phase I/II trial ( 65 ), by providing new insight into the players in the bone marrow niche involved in this pathway. Interestingly, new data in vitro has shown that SDF-1α stimulation of CXCR4 on MM cells may up-regulate the expression of IL-6 through the activation of the PI3K/AKT, suggesting that the IL6 and CXCR4/CXCL12 pathways overlap in MM cells ( 64 ). Overall, our study provides insight into the mechanism of action of drugs targeting the CXCL12/CXCR4 axis, the IL6/IL6R axis, or other SASP protein signaling pathways in MM, and suggests that targeting proteins identified herein may lead to new therapeutic avenues.…”
Section: Discussionmentioning
confidence: 99%
“…The coculture of MM cells with BMSCs increased the drug resistance and suppressed the cell death of MM cells. Consequently, Liu et al demonstrated that SDF-1α-induced interleukin-6 (IL-6) upregulation-mediated drug resistance and apoptosis of MM cell lines in the adhesion state [56]. The report mentioned that SDF-1α treatment-induced PI3K and AKT phosphorylation in MM cells.…”
Section: Roles Of Sdf-1α/cxcr4 On Drug Resistance In MMmentioning
confidence: 99%
“…Recently, a study indicated that when coculture RPMl‐8226 cells with BMSCs, MM cells showed increased level of drug resistance and cell survival. It is attributed to IL‐6, which was upregulated by SDF‐1/CXCR4 causing the activation of the P13K/AKT signaling pathway, thereby affecting the drug resistance mediated by adhesion in MM cells 47 . Enhanced insulin‐like growth factor (IGF‐1) by IL‐6 upregulates MCL‐1 transcription and induces MCL‐1 dependence.…”
Section: Mechanisms Of Drug Resistance Of Pismentioning
confidence: 99%